Women health and development: draft resolution proposed by the delegations of Bulgaria, Cameroon, Canada, China, Denmark, Finland, France, Ghana, Iceland, India, Israel, Jamaica, New Zealand, Norway, Papua New Guinea, Poland, Sweden, United Kingdom of Great Britain and Northern Ireland - World Health Assembly, 44 (World Health Organization, 1991)
(Agenda item 20)